ChemInform Abstract: Catalytic Total Hydrodeoxygenation of Biomass‐Derived Polyfunctionalized Substrates to Alkanes. Issue 27 (18th June 2015) - Nakagawa, Yoshinao; Liu, Sibao; Tamura, Masazumi; Tomishige, Keiichi
Abstract Review: [59 refs.